Participants' perspectives on making and maintaining behavioural changes in a lifestyle intervention for type 2 diabetes prevention: a qualitative study using the theory domain framework. Issue 6 (28th June 2013) - Penn, Linda; Dombrowski, Stephan U; Sniehotta, Falko F; White, Martin
Abstract : Objectives: In a qualitative substudy, we sought to elicit participants' perspectives of their behavioural change and maintenance of new behaviours towards intervention optimisation. Setting: The intervention was delivered in leisure and community settings in a local authority, which according to the UK government statistics ranks as 1 of the 10 most socioeconomically deprived areas in England. Participants: We recruited 218 adults aged 40–65 years at elevated risk of type 2 diabetes (Finnish Diabetes Risk Score≥11) to the intervention. Follow-up at 12 months was completed by 134 (62%). We recruited 15 participants, purposively sampled for physical activity increase, to the qualitative substudy. Intervention: Lifestyle intervention can prevent type 2 diabetes, but translation to service provision remains challenging. The 'New life, New you' intervention aimed to promote physical activity, healthy eating and weight loss, and included supervised group physical activity sessions. Behavioural change and weight loss at 12-month follow-up were encouraging. Design: We conducted 15 individual semistructured interviews. The Framework approach, with a comparison of emerging themes, was used in analysis of the transcribed data and complemented by the Theory Domains Framework. Results: Themes emerging from the data were grouped as perceptions that promoted initiating, enacting and maintaining behavioural change. The data were then categorised in accordance with the Theory Domains Framework: intentions and goals; reinforcement; knowledge; social role and identity; social influences; skills and beliefs about capabilities; behavioural regulation, memory, emotion, attention and decision processes and environmental context and resources. Participant perceptions of intervention features that facilitated behavioural change processes were then similarly analysed. Conclusions: Social influences, reference to social role and identity (eg, peer support), and intentions and goals (eg, to lose weight) were dominant themes across the three phases of behavioural change. Reinforcement, regulation and decision processes were more evident in the maintenance phase. The socioeconomic status of participants was reflected in the environmental context and resource theme. Analysis of phases and theoretical domains of behavioural change added depth and utility to inform intervention optimisation. We will develop the intervention with improved peer support and explicit monitoring of the behavioural change techniques used, prior to a definitive trial.